A literature-based study of patient-centered care and communication in nurse-patient interactions: barriers, facilitators, and the way forward - Abukari Kwame; Pammla M. Petrucka (BMC, 2021)
Abstract Providing healthcare services that respect and meet patients' and caregivers' needs are essential in promoting positive care outcomes and perceptions of quality of care, thereby fulfilling a significant aspect of patient-centered care requirement. Effective communication between patients and healthcare providers is crucial for the provision of patient care and recovery. Hence, patient-centered communication is fundamental to ensuring optimal health outcomes, reflecting long-held nursing values that care must be individualized and responsive to patient health concerns, beliefs, and contextual variables. Achieving patient-centered care and communication in nurse-patient clinical interactions is complex as there are always institutional, communication, environmental, and personal/behavioural related barriers. To promote patient-centered care, healthcare professionals must identify these barriers and facitators of both patient-centered care and communication, given their interconnections in clinical interactions. A person-centered care and communication continuum (PC4 Model) is thus proposed to orient healthcare professionals to care practices, discourse contexts, and communication contents and forms that can enhance or impede the acheivement of patient-centered care in clinical practice.